FROM BRAINROT TO DIGITAL DISCOURSE: STUDENT PRAGMATIC COMMUNICATION IN MEME CULTURE - Sastika Seli; Moh. Hafidz Albadiri; M. Thoriqul Khoir; Cindy Liana Puspitasari; Dinda Prameswari (Universitas PGRI Palembang, 2026)
This study investigates university students’ engagement with brain rot and meme culture within digital communication environments, focusing on the pragmatic functions embedded in meme-based interactions and the extent to which meme culture shapes students’ digital discourse and communication practices. Employing a mixed-methods research design, the study involved undergraduate students as participants. Data were gathered through questionnaires, semi-structured interviews, and pragmatic competence assessments, and subsequently analyzed using both quantitative and qualitative techniques. The findings reveal that meme culture has become deeply embedded in students’ everyday digital interactions, serving multiple pragmatic purposes in online communication. Memes function not only as tools for entertainment and social bonding but also as mechanisms for expressing attitudes, negotiating meaning, conveying humor, and facilitating contextual understanding in digital discourse. Furthermore, the results indicate that sustained exposure to meme culture significantly influences students’ communicative behavior, shaping their interpretation of messages, language use, and interactional strategies in online environments. The study concludes that memes should be viewed as more than merely recreational digital artifacts; they constitute meaningful communicative resources that support effective digital interaction and contribute to the development of pragmatic competence among university students. These findings underscore the growing significance of meme culture as a linguistic and sociocultural phenomenon in contemporary digital communication.